2018
DOI: 10.1103/physrevd.98.044012
|View full text |Cite
|
Sign up to set email alerts
|

Wormhole geometries supported by three-form fields

Abstract: In this work, we find novel static and spherically symmetric wormhole geometries using a threeform field. By solving the gravitational field equations, we find a variety of analytical and numerical solutions and show that it is possible for the matter fields threading the wormhole to satisfy the null and weak energy conditions throughout the spacetime, when the three-form field is present. In these cases, the form field is responsible for supporting the wormhole and all the exoticity is confined to it. Thus, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…We also should understand if the physics of a linkage between Equation (33) and Equation (34) play a role as well. 6) Finally, and not least is to see if our feed into Equation (33) to Equation (34) and linkages to Figure 1, have in their genesis, the methodologies discussed in [34], i.e. as brought up in Phase transitions and the renormalization group as brought up by Jean-Zinn-Justin, which has a very interesting discussion of the Nancy Kerrigan problem, i.e.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…We also should understand if the physics of a linkage between Equation (33) and Equation (34) play a role as well. 6) Finally, and not least is to see if our feed into Equation (33) to Equation (34) and linkages to Figure 1, have in their genesis, the methodologies discussed in [34], i.e. as brought up in Phase transitions and the renormalization group as brought up by Jean-Zinn-Justin, which has a very interesting discussion of the Nancy Kerrigan problem, i.e.…”
Section: )mentioning
confidence: 99%
“…4) Should there be a linkage between an initial worm hole style start to the formation of the observable universe, as a compliment to the big bank/inflation metrics, the author strongly recommends a review of the article given by Bruno J. Barros and Francisco S. N. Lobo as to relevant Wormhole geometry [33], and the question of negative energy states in a wormhole threat. If as may be the case in nonsingular starts to the expansion of the universe, negative energy states make an appearance, this may be a clue as to what is called f(R) geometries which in turn may have relevance to some of the polarization states in [32].…”
Section: And What About Polarization States Especially If We Have Mamentioning
confidence: 99%
“…[41], to obtain spherically symmetric solutions. Some of these solutions can be interpreted as black holes by identifying the existence of event horizons (wormhole solutions were also found in [42]). The others can be interpreted as naked singularities in which there is no event horizon in the spacetime.…”
Section: Regular Black Hole Supported By 3-formmentioning
confidence: 99%
“…The employment of three-form fields in gravitation was analyzed in [47], where wormhole solutions in a static and spherically symmetric spacetime continuum were explored. It was found that it is possible for the ordinary matter fields threading the wormhole to obey the classical energy conditions throughout the spacetime, while the three-form field holds the wormhole open, violating the null and weak energy conditions.…”
Section: (): V-volmentioning
confidence: 99%